NEW DIDACTIC CONCEPTION FOR THE TEACHING PROCESS - LEARNING THE ZOOLOGY OF THE CORDADOS - Armiñana-García, Rafael (2020)
This research proposes and validates a new Didactic Conception with an ecosystem approach for the teaching - learning process of the zoology of the chordates in the third year of the Regular Day Course, of the Bachelor Degree in Biology Education of the Faculty of Media Education "Félix Varela Morales" of the Central University "Marta Abreu" of Las Villas, Villa Clara, Cuba. The information for the diagnosis is obtained from the application of different empirical methods such as surveys, interviews, observation and review of documents. The Didactic conception is based on the Historical - Cultural Theory of LS Vygotsky and his followers, in which an ecosystem approach and confrontation to climate change is demonstrated, which, from its implementation in the aforementioned race, allows students to become even more aware of the imperative need to conserve biological diversity, as well as developing intellectual, practical and computer skills in them. To put this concept into practice, a new program was developed for the study of the zoology of the chordates with the textbook "Zoology of Chordates" using an ecosystem approach, a system of virtual practical classes for the study of external and internal morphology of different vertebrates never before introduced, and a collection of concept maps in electronic format. The new Didactic Conception is submitted for evaluation at the discretion of experts and was implemented in the academic courses 2017 - 2018 and 2018 - 2019, with satisfactory results. Key words: Concepcion Didactics – ecosystem approach – learning process – teaching – Zoology of the chordates